Perceived performance of activities of daily living by stroke patients: key in decision to call EMS and outcomes - Tarantini, Luca; Merzou, Fatma; Luley, Maxine; Rollmann, Aline; Schwindling, Michael Peter; Lesmeister, Martin; Gläss, Marietheres; Wollenburg, Jennifer; Schwindling, Lenka; Fassbender, Klaus (Frontiers in Neurology, 2023)
Background: Until recently, public education campaigns aimed at improving help-seeking behavior by acute stroke patients have achieved only limited or even no effects. Better understanding of psychological factors determining help-seeking behavior may be relevant in in the design of more effective future campaigns. Methods: In this prospective, cross-sectional study, we interviewed 669 acute stroke patients within 72 hours after hospital admission. The primary endpoint was the effect of psychological factors on the decision to call emergency medical services (EMS). Secondary endpoints were the effects of such factors on treatment rates and clinical improvement (difference between modified Rankin scale scores at admission and at discharge). Results: Only 48.7% of the study population called the EMS. Multivariate logistic and linear regression analyses revealed that perception of unimpaired performance of activities of daily living (ADL) was the only psychological factor that predicted EMS use and outcomes. Thus, patients who perceived only minor impairment in performing ADL were less likely to use EMS (odds ratio, 0.54 [95% CI, 0.38–0.76]; p = 0.001), had lower treatment rates, and had less improvement in modified Rankin scale scores (b = 0.40, p = 0.004). Additional serial mediation analyses involving ischemic stroke patients showed that perception of low impairment in ADL decreased the likelihood of EMS notification, thereby increasing prehospital delays, leading to reduced thrombolysis rates and, finally, to reduced clinical improvement. Conclusion: Perception of unimpaired performance of ADL is a crucial barrier to appropriate help-seeking behavior after acute stroke, leading to undertreatment and less improvement in clinical symptoms. Thus, beyond improving the public’s knowledge of stroke symptoms, future public education campaigns should focus on the need for calling the EMS in case of stroke symptoms even if daily activities do not seem to be severely impaired.